2009
DOI: 10.5483/bmbrep.2009.42.3.148
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine dithiocarbamate-induced activation of ERK and increased expression of c-Fos in mouse embryonic stem cells

Abstract: Pyrrolidine dithiocarbamate (PDTC) is a stable anti-oxidant or pro-oxidant, depending on the situation, and it is widely used to inhibit the activation of NF-κB. We recently reported that PDTC activates the MIP-2 gene in a NF-κB-independent and c-Jun

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, previous studies have shown that Erk1/2 MAPK plays an important role in activation of the AP1 transcription complex comprising c-Fos and c-Jun family members (7,18,26,37,53,57). Our current studies demonstrate that LA CS induced an increase in Erk1/2 MAPK phosphorylation in Caco-2 cells within 1 h that persisted for 24 h. Parallel to an increase in Erk1/2 MAPK phosphorylation at 24 h, LA CS also induced protein expression levels of c-Fos and c-Jun in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have shown that Erk1/2 MAPK plays an important role in activation of the AP1 transcription complex comprising c-Fos and c-Jun family members (7,18,26,37,53,57). Our current studies demonstrate that LA CS induced an increase in Erk1/2 MAPK phosphorylation in Caco-2 cells within 1 h that persisted for 24 h. Parallel to an increase in Erk1/2 MAPK phosphorylation at 24 h, LA CS also induced protein expression levels of c-Fos and c-Jun in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that c-Fos and c-Jun transcription factors are activated by the Erk1/2 MAPK pathway (7,18,26,37,53,57). Our previous studies showed that stimulation of Pgp function by LA CS was mediated via an Erk1/2 MAPK pathway (48).…”
Section: La Cs Induces Erk1/2 Mapk Activation and C-fos Or C-jun Protmentioning
confidence: 99%
“…Differentiation was shown to be promoted in mouse ESC when NF-kB proteins were inhibited by pyrrolidine dithiocarbamate (PDTC), promoting ERK1/2 signaling and, therefore, differentiation. 80 In this situation, the authors described that FOS protein was also present. This relation suggests that the presence of FOS and the inhibition of NF-kB are inadequate for cellular reprogramming.…”
Section: Paper Molecular Biosystemsmentioning
confidence: 99%
“…Pomc-a , pomc-b , and pomc-c cDNA have been cloned in Jpn flounder (Kim et al, 2009 and accession number ACG68732); the original terms POMC-II, POMC-I, and POMC-III in the paper correspond to POMC-A, POMC-B, and POMC-C, respectively. We observed the expression of these three genes in the pituitary and those of pomc-c in Jpn flounder skin.…”
Section: Pomc and MC Peptides In Floundersmentioning
confidence: 99%